Pooling in Two-Location Inventory Systems with Non-Negligible Replenishment Lead Times - Tagaras, George; Cohen, Morris A. (Management Science, 1992)
This paper deals with the analysis of two-location periodic review inventory systems with non-negligible replenishment lead times. Emergency transshipments are used in these systems as a recourse action to reduce the occurrence of shortages. A class of partial pooling policies is proposed for the control of transshipments. The cost performance of this class of policies is shown to be inferior to that of complete pooling. An approximate model and a heuristic algorithm are introduced to compute near-optimal stocking policy solutions. Comparisons with simulation results verify the satisfactory performance of the approximate model and algorithm. Numerical sensitivity analysis provides additional insight into the nature of optimal transshipment behavior.